2010
DOI: 10.1083/jcb1914oia9
|View full text |Cite
|
Sign up to set email alerts
|

Real-time analysis of T cell receptors in naive cells in vitro and in vivo reveals flexibility in synapse and signaling dynamics

Abstract: The real-time dynamics of the T cell receptor (TCR) reflect antigen detection and T cell signaling, providing valuable insight into the evolving events of the immune response. Despite considerable advances in studying TCR dynamics in simplified systems in vitro, live imaging of subcellular signaling complexes expressed at physiological densities in intact tissues has been challenging. In this study, we generated a transgenic mouse with a TCR fused to green fluorescent protein to provide insight into the early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 37 publications
2
32
0
1
Order By: Relevance
“…Our findings have reminiscence of the initial characterization, by multiphoton imaging, of phases of T cell motility during lymph node priming (17, 18), which has fueled ongoing works to under-stand cell-cell interactions and the biology of T cells during each phase. We do note that the apparent lack of antigen recognition may mask weak antigen recognition, as multiple studies have documented "motile synapses" that are effective in some elements of signaling in vivo (42)(43)(44). That these late-phase interactions are likely antigen independent is supported by the apparent lack of a role for either TCR stimuli (e.g., ZAP70) or the appearance of TCR-induced signals (e.g., NUR77), although signals might be generated but are just too weak for these methods to detect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings have reminiscence of the initial characterization, by multiphoton imaging, of phases of T cell motility during lymph node priming (17, 18), which has fueled ongoing works to under-stand cell-cell interactions and the biology of T cells during each phase. We do note that the apparent lack of antigen recognition may mask weak antigen recognition, as multiple studies have documented "motile synapses" that are effective in some elements of signaling in vivo (42)(43)(44). That these late-phase interactions are likely antigen independent is supported by the apparent lack of a role for either TCR stimuli (e.g., ZAP70) or the appearance of TCR-induced signals (e.g., NUR77), although signals might be generated but are just too weak for these methods to detect.…”
Section: Discussionmentioning
confidence: 99%
“…be an indicator of T cell recognition of antigen-presenting cells (APCs) (17,18), although we and others have shown that TCR triggering can also occur without substantial stopping (19)(20)(21) and lead to a "motile synapse" (or sometimes "kinapse"). Other factors may also modulate motility; integrins may either speed up (22) or slow down (23) migration, and chemokines can either induce faster scanning (22) or "tether" cells in place (24).…”
Section: Introductionmentioning
confidence: 99%
“…Such a dispersed and transient activation pattern could prove sufficient to induce efficient TCR internalization, similarly to the situation described for motile naïve T cells in lymph nodes. 28 However, it may not enable sustained calcium mobilization. This hypothesis is supported by the finding that recently activated T cells forming kinapses in vivo engage their TCR efficiently but fail to accumulate the signaling molecule LAT at the IS and emit only short calcium spikes.…”
Section: Discussionmentioning
confidence: 99%
“…Kinapses can also be observed in the late phase of activation when T cells have been visualized swarming antigen-bearing APCs (1,9) as well as during interactions between follicular helper T cells and germinal center B cells (12). At least in some instances, kinapses can result in measurable TCR signaling, as visualized by TCR internalization, Ca 2+ elevation, and shedding of CD62L (11)(12)(13)(14). Therefore, T cells can effectively couple motility and integration of activation signals.…”
mentioning
confidence: 99%